Photochemical Study of Cobalt (II) in Dimethyl Sulfoxide, Simethylformamide and Chloroform Solvents - Ibrahim, Farah; Zageer, Dheaa; Fadhil, Duha; Adil, Hadeel; Yousif, Emad; Hussain, Zainab (Al-Nahrain Journal of Science, 2018)
The photochemistry of chelate complex 2-(6-methoxynaphthalen-2-yl) propanoic acid cobalt (II) Co(L)2 was studied in three polar aprotic solvents: Dimethyl sulfoxide (DMSO), Dimethylformamide (DMF) and chloroform (CHCl3). Monochromatic light of wavelength 311 nm was used for the irradiation process at 25oC. Uv-visible spectral changes indicated an intra oxidation-reduction reaction occuring during the photolysis of Co(L)2 complex, with homolytic scission of Co-L bond. The quantum yield (d), rate of photodecomposition and reactivity ratio (k2/k-1) was determined in each solvent. These values always increase as the polarity of the solvent increases and follow the order: DMSO > DMF > CHCl3 The mechanism of photodecomposition of this complex under the applied conditions was proposed.